Development and evaluation of culture-based digital sandpaper letters as an effective learning medium for slow learner students in recognizing and writing letters - Abdurrahman, Ginanjar; Sintawati, Mukti; Zakiyyah , Amalina Maryam (Universitas Ahmad Dahlan, 2023)
This study addresses the educational challenges faced by slow learner students, who exhibit lower cognitive abilities than their peers, particularly in the context of reading difficulties during elementary school. Recognizing the need for targeted interventions, this research focuses on the development of a culture-based digital sandpaper letter learning medium tailored to enhance the letter recognition and writing skills of slow learner students. The research employs a 4D development model, encompassing define, design, development, and dissemination phases. The sandpaper letters, featuring rough textures, serve as a sensory-motor stimulus to facilitate the learning process for slow learner students. Culturally relevant themes from Indonesia, such as dances, songs, musical instruments, names of weapons, tribes, food, and place names, are incorporated into the design to enhance engagement and connection with the material. Expert assessment sheets and teacher response questionnaires are utilized as assessment instruments. Results indicate that the developed learning medium is validated by experts and deemed practical by teachers. Furthermore, research trials demonstrate the effectiveness of the culture-based digital sandpaper letters in facilitating letter recognition and writing skills among slow learner students. This innovative approach not only addresses the specific needs of this student population but also contributes to the broader field of inclusive education.